Exclusive use of fixed pressure valves for cerebrospinal fluid diversion in a modern adult cohort. Issue 12 (December 2018) - McDowell, Michael M.; Chiang, Michael C.; Agarwal, Nitin; Friedlander, Robert M.; Wecht, Daniel A.
Abstract: Background: There is extensive debate on the role of fixed pressure shunts in the adult population. Most studies assessing fixed pressure valves do not consider the potential for changes in technique and management of shunts. We sought to examine the natural history of fixed pressure. Methods: We conducted a retrospective chart review of 169 patients undergoing shunt placement by the senior author Daniel Wecht (DW). The etiology of shunt placement, shunt failure rates, and outcome data was assessed for each patient. Results: Overall, 126 patients underwent initial shunt placement. Thirty-three (26.2%) patients required at least one shunt revision during follow-up. The most common cause of first time revision was mechanical shunt malfunction (13, 39.4%), followed by infection (7, 21.2%), and shunt migration (6, 18.2%). Three patients (9.1%) required revision due to misplaced catheters. Underdrainage or overdrainage of shunts each resulted in revisions for 2 (6.1%) patients. The mean follow-up length was 28.1 ± 6.1 months. Conclusion: Fixed pressure shunts failed primarily because of shunt malfunction and occurred most commonly in patients developing hydrocephalus as a result of hemorrhage or normal pressure hydrocephalus (NPH). The overall failure rate between these two groups was proportionally equivalent. Both overdrainage or underdrainage were found to be rare indications for revision.